Coleoptera insekts of coastal ecosystems of Russian part of Caspian Sea - S. M. Klicheva; Z. M. Karaeva; R. I. Inkovasova; G. M. Abdurahmanov (Юг России: экология, развитие)
The article lists the complex of Coleoptera typical for the different coastal ecosystems.